GHI Launch Des Moines 2012 - Mogge, Mathias (2012)
2012 Global Hunger Index Launch Event "The Challenge of Hunger: Ensuring Sustainable Food Security Under Land, Water & Energy Stresses" by Mathias Mogge (Welthungerhilfe) October 18, 2012